A DESCRIPTIVE ANALYSIS OF SLANG TERMS IN SCARFACE MOVIE - Martin Carlos; Nurhaeda Gailea; Rosmania Rima (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2019)
This research concerns with the use of slang terms in Scarface movie and proposes some problems; what slang that used in the movie? , how are the word formation of the slang? and the meaning of slang that used in the movie. This research uses a descriptive qualitative method to classify and analyze the utterances. After investigating the utterances of the movie script, the researchers found several findings on it. First, there are forty seven slang that used in the movie, such as; ain’t, shit, and gotta. Second, the result of word formation of slang according to Yule’s theory, there are: eight borrowing, five blending, four clipping, one multiple process, six compounding and one back formation. The last is describing the literal and figurative meaning of the slang words according to NTC’s Dictionary of American Slang and Colloquial.